Kualitas Pelayanan, Akuntabilitas, dan Transparansi Informasi Keuangan Terhadap Kepercayaan Masyarakat: Studi Pemerintah Kecamatan Laweyan Surakarta - Anggara Hendra Saputra; Indra Lila Kusuma; LMS Kristiyanti (Nur Science Institute, 2026)
This study aims to analyze the effect of service quality, accountability, and transparency of financial information on public trust in Laweyan District. The research method used is quantitative with a survey approach. The sample in this study amounted to 100 respondents consisting of sub-district/urban village service and finance officials, RT heads, and the general public. Data analysis techniques used include descriptive statistical tests, data instrument tests, classical assumption tests, and hypothesis tests with the help of SPSS software version 23. The results of the regression test show that service quality has a significant effect on public trust, which means that the better the public service provided, the more public trust will increase. Accountability has also been shown to have a significant effect, indicating that clear accountability for financial management and government performance encourages public trust. Furthermore, transparency of financial information also has a significant effect, indicating that openness of information on public fund management can increase public trust in the government. These findings indicate that improving service quality, accountability, and transparency together can strengthen public trust in the Laweyan District government.